UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN KARIKA (Carica pubescens) DENGAN METODE DPPH BESERTA IDENTIFIKASI SENYAWA ALKALOID, FENOL DAN FLAVONOID - Indranila Indranila; Maria Ulfah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Antioxidant is a compound that can inhibit free radicals. Free radicals can cause several diseases. The purpose of this study is to reveal the antioxidant activity of carica leave ethanol extract (CLEE) (Carica pubescens) and determine its active compounds. The extract produces with maceration method using ethanol 96% as a solvent. The antioxidant activities of CLEE series concentration (2.5; 5.0; 10.0; 15.0; 20.0 and 25.0) ppm and vitamin C series concentration of (0.5; 1.0; 1.5; 2.0 and 2.5) ppm as standard antioxidant were measured with DPPH method. Absorbance was observed by spectrophotometer UV-Vis. Antioxidant activities presented by IC50 value derived from probit analysis. Identification of active compounds in CLEE was performed by Thin Layer Chromatography (TLC) method. The results showed that the IC50 value for CLEE and vitamin C as an antioxidant were 30.8 ppm and 2.9 ppm respectively. Base on TLC analysis, alkaloids, a phenol compound, and flavonoids were found in CLEE. Key words: antioxidant, Carica pubescens, DPPH, TLC